Re-configuring inclusion, decolonising practice: Digital participation and learning in Black women's community-led heritage. Issue 2 (November 2016) - Clarke, Rachel; Lewis, Rosie M
This article explores an innovative model of adult education within museums developed from a Black feminist approach. BAM! Sistahood! is a community-led project with regional heritage organisations, universities and women's centres in the UK, that offers a holistic approach to heritage development. The ethos is to challenge the perpetuation of existing Eurocentric models of heritage and the historical exclusion experienced by black, Asian, minority ethnic and refugee (BAMER) women when accessing museums and archives. We argue that to be transformative, adult education processes must be sensitive to barriers in participation and encourage shared learning opportunities and change within institutions. Digital technology is an important feature, if configured carefully, enabling alternative models of women's expertise to be documented and shared.